Barriers and facilitators for transitioning of young people from adolescent clinics to adult ART clinics in Uganda: unintended consequences of successful adolescent ART clinics - Scovia Nalugo Mbalinda; Sabrina Bakeera-Kitaka; Derrick Amooti Lusota; Eleanor Namusoke Magongo; Philippa Musoke; Dan Kabonge Kaye (BMC, 2020)
Abstract Background There is a growing number of adolescents and young adults living with HIV (YPLHIV) who require the transfer of care from pediatric/ adolescent clinics to adult Antiretroviral therapy (ART) clinics. A successful transition is critical for optimum health outcomes, yet facilities may lack infrastructure, human resources (with appropriate knowledge and skills), and a supportive environment, as only 3% of clinics in Uganda caring for YPLHIV have a process for supporting this critical transition from pediatric to adult care, and, facilitators and barriers of a successful transition are not well documented. The purpose of this study was to explore the facilitators and barriers of transitioning among adolescents from adolescent clinics to adult ART clinics. Method Eighteen focus group discussions were held in nine health facilities with 174 adolescents and YPLHIV to assess barriers and facilitators regarding transitioning to adult clinics. The focus group discussions were audio-recorded and transcribed. The Silences Framework using a thematic approach guided the analysis. Results The key emerging issues were: Unfriendly adults in adult clinics, Care provided in the adolescent clinics, fear of stigma from health care providers, Congestion and long waiting time, fear to lose friends were barriers to transitioning. Transitioning preparation is key to a successful transition, moving as a cohort facilitates transition, and care in adult clinics offers new opportunities, could facilitate readiness and transition. Conclusion YPLHIV expressed fear to transition to adult clinics mainly because of the perceived better care provided in the adolescent clinic, thus constituting a barrier to smooth transition A range of individual, social and health system and services-related factors hindered transitioning. The expectation of transitioning as a group, assurance of similar care as in the adolescent clinic, and guarantees of confidentiality, privacy, and autonomy in decision-making for care was perceived as facilitators. Understanding barriers and facilitators can enable the Ministry of Health to improve the quality of life of YPLHIV through linkage to care, adherence, retention, and viral suppression. There is a need to better planning and preparation for clinical providers and YPLHIV with a focus on age-appropriate and individualized case management transition as well as focus on improving both clinical and psychosocial support throughout the process.